Tourist-cultural advertising of Old Havana, Cuba. Case study during 2021. - Labañino, José; Godoy Guevara, Gandhy; Ojeda La Serna, Vivian (Revista Ecos de la Academia, 2022)
Old Havana is a tourist site with great cultural attractions and one of the most visited destinations in the Caribbean. The objective of the research is to explore the operation of the tourist-cultural promotion, through the advertising campaigns carried out by the different institutions, analyzing the actions and strategies used in the execution of the advertising message. In this qualitative research, interviews were applied to experts in tourism in Old Havana, the documentary technique allowed the study of statistics related to tourism and the observation contextualized the behavior of foreign and national tourists from their nature. As the main results, it was found that tourism advertising aimed at the international public tends to generalize in the destination Cuba, without focusing on each small tourist area. As a conclusion, we obtain that the use of culture for the promotion of tourism is limited to the background of the different campaigns, since the Old Havana destination plays a mainly passing role in the planning of foreign tourists, prioritizing the destinations of Sun and Beach.
Keywords: Old Havana; tourist site; tourism; culture; advertising campaigns